Alemtuzumab in the treatment of multiple sclerosis - Fernandez Ó (Dove Medical Press, 2014)
Óscar Fernandez Institute of Clinical Neuroscience, Neurology Department, Hospital Regional Universitario Carlos Haya, FIMABIS, Malaga, Spain Abstract: Alemtuzumab (formerly known as Campath-1H) has recently been approved by the European Medicines Agency for highly-active, relapsing-remitting multiple sclerosis (MS). The molecule targets the CD52 surface glycoprotein on certain T cells and B cells and is thought to exert its effect in MS through a “resetting” of the lymphocyte population. Approval was granted on the strength of two pivotal studies, Comparison of Alemtuzumab and Rebif® Efficacy in Multiple Sclerosis (CARE-MS)-1 in the first-line setting and CARE-MS-2 in patients who had failed first-line therapy. In both studies, alemtuzumab significantly reduced the relapse rate compared to the comparator, interferon beta-1a (44 µg) given subcutaneously three-times per week (Rebif®). In the first-line study, alemtuzumab was also found to significantly reduce the number of patients with sustained progression compared to interferon beta-1a therapy. Autoimmune disorders represent the major side effect of alemtuzumab therapy although they can be managed by careful monitoring and early treatment. Overall, alemtuzumab is likely to be a valuable addition to the neurologist´s armamentarium for the treatment of relapsing-remitting MS. Keywords: alemtuzumab, multiple sclerosis, new therapies, interferon beta-1a, monoclonal antibody, treatment